Serum levels of 25-hydroxy vitamin D in psoriatic patients - Zuchi, Manuela Ferrasso; Azevedo, Paula de Oliveira; Tanaka, Anber Ancel; Schmitt, Juliano Vilaverde [UNESP]; Martins, Luis Eduardo Agner Machado (Soc Brasileira Dermatologia, 2015)
Studies have shown a relationship between vitamin D and psoriasis. We compared serum levels of vitamin D of 20 psoriasis patients and 20 controls. The median vitamin D level was 22.80 +/- 4.60 ng/ml; the median in the cases was 23.55 +/- 7.6 ng/ml, and in controls 22.35 +/- 3.10 ng/ml (p = 0.73). Only 2 cases and 4 controls had sufficient levels of vitamin D, although without statistical significance between the groups (p = 0.608). Levels were lower in women with psoriasis compared with those in male patients (20.85 +/- 6.70 x 25.35 +/- 2.90 ng/ml, p = 0.03), a finding that was not observed among controls.
Keywords: Psoriasis; Vitamin D; Vitamin D deficiency